Hydrogen peroxide assisted advanced electrocoagulation for reducing the organic content of leachate nanofiltration concentrate - Varank, Gamze; Guvenc, Senem Yazici; Can-Guven, Emine; Yokus, Senem; Bilgin, Oyku Nur (ELSEVIER SCIENCE INC, 2024)
Integrated biological treatment-membrane filtration is widely applied in leachate treatment to ensure discharge standards. The most important waste of this integrated application is high volumes of membrane concentrate. In this study, the treatment of leachate nanofiltration concentrate (NFC) with high resistive organic matter content was investigated by hydrogen peroxide (HP) assisted advanced electrocoagulation process (EC-HP) using Al electrodes. To achieve maximum pollutant removal efficiencies, process optimization was carried out using the Box-Behnken design (BBD). Statistically, the fit of the model was evaluated by analysis of variance. Correlation coefficients (R2) of all mathematical models developed for system responses (COD, UV254, TOC, and color removal efficiency) with EC-HP process were close to 1, adjusted R2 values were close to R2 values, and the difference between adjusted R2 and predicted R2 values was less than 0.2. These values indicate that the BBD method is effective, appropriate, and meaningful in explaining the pollutant removal from leachate NFC with the EC-HP process. Under the optimized conditions (27.3 mM HP, 0.6 A, pH 5, and 45 min) 62.2 %, 55.3 %, 73.9 %, and 85.9 % COD, TOC, UV254, and color removal efficiencies, respectively were predicted by the model and by validation study, 57.3 % COD, 52.0 % TOC, 68.3 % UV254, and 85.0 % color removal yields were achieved. SEC and SECCOD values were calculated as 7.65 kWh/m3 and 2.78 kWh/kgCOD, respectively at optimum conditions. Moreover, ENC, ELC, CC, and TC values were 0.55 $/m3, 0.82 $/m3, 8.0 $/m3, and 9.37 $/m3, respectively. The results of the study showed that the EC-HP process is an effective method for pollutant removal from leachate NFC.
Keywords: Advanced Electrocagulation; Box-Behnken Design; Leachate; Nanofiltration Concentrate; ADVANCED OXIDATION PROCESSES; ELECTRO-FENTON PROCESS; WASTE-WATER TREATMENT; LANDFILL LEACHATE; ELECTROCHEMICAL PROCESSES; CURRENT-DENSITY; POST TREATMENT; REMOVAL; COAGULATION; ELECTROOXIDATION; Chemistry; Engineering